Analysis juridical implementation of occupational health and safety and social security/BPJS employment for workers in notary offices - Ilwira Fakhrurrazi Lubis; Siti Hajati Hoesin (The International Journal of Politics and Sociology Research, 2023)
This research uses normative juridical research methods which are used to analyze the effectiveness of Law of the Republic of Indonesia Number 2 of 2014 concerning the Position of Notary Public, Law Number 40 of 2004 concerning the National Social Security System and Law Number 24 of 2011 concerning the Social Security Organizing Body for Notary Workers play a crucial role in aiding Notary performance in serving deed making services, such as assisting in preparing for making, registering, and validating private letters and deeds and serving as a witness at the inauguration of a deed (Instrumentair Witness). Workers are a crucial component of a Notary's duties and responsibilities, as they hold a strategic position in the process of creating a document; without workers, the Notary's design cannot be carried out as intended. Therefore, the existence of Notary employees must be taken into account so that they can carry out the Notary's instructions effectively.